The Development Of Islamic Economics Based On Halal Tourism In Indonesia - Ade Irma; Fitri Yani (Proceeding International Seminar of Islamic Studies, 2019)
: This paper describes the development of Islamic economic based on halal tourism in Indonesia. Tourism and economy have a close relationship, the development of tourism in a region will develop the economy of the region. The tourism sector is one sector that is able to increase employment and economic growth. The relations between both of them are complementary, the economy will grow if tourism development is more advanced. The tourism sector is Indonesia’s mainstay in gaining foreign exchange. The Badan Pusat Statistik (BPS) released the number of foreign tourist visits to Indonesia during 2018 to reach 15.81 million or an increase of 12.58 %. In 2018 foreign exchange from the tourism sector accounted for US 17 billion, an increase of 11.8 %. The Indonesian government targets 20 million foreign tourist visits in 2019. The ministry of tourism is targeting 25 % or equal to 5 million of foreign tourists are Muslim tourists. Indonesia has a great opportunity in developing the halal tourism sector. Bank Indonesia (BI) states that halal tourism also supports the development of the Islamic Economics. In 2019 Indonesia was ranked first in the category of the world’s best halal tourism destinations based on the Global Muslim Travel Index (GMTI ) standards.